Handling and transport of cattle and pigs in South America - Paranhos Da Costa, Mateus J.R. [UNESP]; Huertas, Stella M.; Strappini, Ana C.; Gallo, Carmen (My University, 2014)
This chapter covers animal handling and transport research in Brazil, Chile and Uruguay. Data collected from 2005 to 2012 clearly show that bruising and other damage to beef and pork carcasses can be greatly reduced by training truck drivers and handlers, and by simple improvements in facilities. Poor design and operation of the door on the beef stunning box caused 36.5% of the bruises. After training and improvements, the percentage of cattle bruised was halved. Cattle that passed through markets on the way to slaughter had four times the risk of having meat of a high pH (>5.8) compared with cattle that were shipped direct. Another advantage of the adoption of low stress handling methods is less stress on the stock people. During cattle truck loading, the elimination of electric prods, hitting and shouting reduced bruising from over two per carcass to less than one. When better methods are used for handling cattle, corrals can be built from less expensive and more economical, for example solid fences that block the animal's vision can be constructed from vertical bamboo strips attached to a wire or wood plank fence. The chapter also provides details of a low cost corral layout and photos of typical South American trucks. The training of handlers and the installation of non-slip floors, solid shields to block cattle vision and head holders improved stunning and reduced both vocalization and the use of electric prods. Further improvements are still needed. In one study, for instance, 17% of the cattle vocalized and 38% struggled in the stun box. A vocalization percentage of 5% or less is an achievable goal.
Keywords: Bruises; Corrals; Electric prods; Loading trucks; Stunning; Welfare